Photocatalytic low-temperature defluorination of PFASs - Zhang, Hao; Chen, Jin-Xiang; Qu, Jian-Ping; Kang, Yan-Biao (Nature (London), 2024)
Polyfluoroalkyl and perfluoroalkyl substances (PFASs) are found in many everyday consumer products, often because of their high thermal and chemical stabilities, as well as their hydrophobic and oleophobic properties 1 . However, the inert carbon–fluorine (C–F) bonds that give PFASs their properties also provide resistance to decomposition through defluorination, leading to long-term persistence in the environment, as well as in the human body, raising substantial safety and health concerns 1 , 2 , 3 , 4 – 5 . Despite recent advances in non-incineration approaches for the destruction of functionalized PFASs, processes for the recycling of perfluorocarbons (PFCs) as well as polymeric PFASs such as polytetrafluoroethylene (PTFE) are limited to methods that use either elevated temperatures or strong reducing reagents. Here we report the defluorination of PFASs with a highly twisted carbazole-cored super-photoreductant KQGZ . A series of PFASs could be defluorinated photocatalytically at 40–60 °C. PTFE gave amorphous carbon and fluoride salts as the major products. Oligomeric PFASs such as PFCs, perfluorooctane sulfonic acid (PFOS), polyfluorooctanoic acid (PFOA) and derivatives give carbonate, formate, oxalate and trifluoroacetate as the defluorinated products. This allows for the recycling of fluorine in PFASs as inorganic fluoride salt. The mechanistic investigation reveals the difference in reaction behaviour and product components for PTFE and oligomeric PFASs. This work opens a window for the low-temperature photoreductive defluorination of the ‘forever chemicals’ PFASs, especially for PTFE, as well as the discovery of new super-photoreductants. Photocatalysis at 40–60 °C is shown to be able to defluorinate perfluoroalkyl substances, known as ‘forever chemicals’, allowing the recycling of fluorine in polyfluoroalkyl and perfluoroalkyl substances as inorganic fluoride salt.